Correlations of Cervical Sagittal Alignment before and after Occipitocervical Fusion - Matsubayashi, Yoshitaka (Global Spine J, 2015)
Study Design Retrospective radiographic study. Objective To investigate changes and correlations of cervical sagittal alignment including T1 slope before and after occipitocervical corrective surgery. We also investigated the relevance for preoperative planning. Methods We conducted a retrospective radiographic analysis of 27 patients who underwent surgery for occipitocervical deformity. There were 7 men and 20 women with a mean age of 56.0 years. Mean follow-up was 68.0 months (range 24 to 120). The radiographic parameters measured before surgery and at final follow-up included McGregor slope, T1 slope, occipito (O)–C2 angle, O–C7 angle, and C2–C7 angle. Pearson correlation coefficient was used to examine the correlation between the radiographic parameters. Results There was a stronger positive correlation between the T1 slope and the O–C7 angle both preoperatively and postoperatively (r = 0.72 and r = 0.83, respectively) than between the T1 slope and the C2–C7 angle (r = 0.60 and r = 0.76, respectively). The O–C2 angle and C2–C7 angle had inverse correlations to each other both pre- and postoperatively (r =  − 0.50 and −0.45). McGregor slope and T1 slope did not significantly change postoperatively at final follow-up. Increase in O–C2 angle after surgery (mean change, 10.7 degrees) inversely correlated with decrease in postoperative C2–C7 angle (mean change, 12.2 degrees). As result of these complementary changes, O–C7 angle did not statistically change. Conclusions Our results suggest that the O–C7 angle is regulated by T1 slope and the corresponding O–C7 angle is divided into the O–C2 and C2–C7 angles, which have inverse correlation to each other and then maintain McGregor slope (horizontal gaze).